"Help me fight my constant battle": A focus group study of overweight and obese women's mHealth app experiences to manage gestational weight gain. (January 2023) - Lee, Ching-Fang; Hsiung, Yvonne; Chi, Li-Kang; Huang, Jian-Pei; Chen, Hung-Hui
Highlights: The core theme for overweight and obese pregnant women to manage GWG is to safely deliver a healthy baby. Main themes identified are: planning to know more and wanting to do right, feeling like a failure and having low self-expectations, struggling with life and desiring for a peace of mind, yearning to be supported and hoping to be seen, and adjusting for the future and embracing new technology. Desired features in the mHealth App include: links to prenatal examinations, auto-reminders, incentives or reward systems, a peer support platform, easy-to-use fingertip control, and an evaluation and tracking system. Abstract: Objectives: To understand and describe overweight and obese pregnant women's mHealth app experiences in managing gestational weight gain (GWG) for optimal weight goals. Design: A focus group study. Setting: We identified and invited pregnant women from a prenatal outpatient clinic in a metropolitan city in Northern Taiwan. Participants: The participants were women whose pre-pregnancy BMI≥25 Kg/m 2 at antenatal booking, and have experience using smartphone apps for pregnancy e-information. A total of 13 overweight and obese women were agreed to participate, their gestation weeks from 11 to 38 weeks. Methods: Three focus group of six sessions were conducted from July to October of 2019. Thematic analysis was employed to inductively analyze the qualitative data. Findings: Overweight and obese pregnant women...s major concern was to safely deliver a healthy baby. Main themes identified included: planning to know more and wanting to do right, feeling like a failure and having low self-expectations, struggling with life and desiring peace of mind, yearning to be supported and hoping to be seen, adjusting for the future and embracing new technology to engage in GWG management. Key conclusions and implications for practice: The core theme was presented as high BMI pregnant women...s shared need to be well-equipped to fight their constant weight battle, reflecting these women...s mixed feelings and barriers toward GWG control and body image during pregnancy. Experiences with a GWG addressing mHealth APP seemed to be positive and further facilitated healthy eating and physical activities, participants... self-efficacy may be increased along with satisfactory APP adherence to prevent excessive GWG for women with obesity.